The Process of Joint Approval Between the Regional Head and the Regional Legislative Council in the Formulation of the Regional Revenue and Expenditure Budget - Rizki Doli Mada Ritonga; Ida Nadirah; Andryan (CERED Indonesia Institute, 2025)
The Regional Revenue and Expenditure Budget (Anggaran Pendapatan dan Belanja Daerah - APBD) constitutes a legal instrument and a financial management guideline aimed at fulfilling public services in accordance with the principle of regional autonomy. This study examines the drafting process of the APBD, the legal standing of the Regional House of Representatives (Dewan Perwakilan Rakyat Daerah - DPRD), and the mechanism for establishing joint approval between the Regional Head and the DPRD within the Government of Labuhanbatu Regency. This research is a normative legal study employing a statutory approach with a descriptive-analytical specification. Data collection was conducted through library research of primary and secondary legal materials, which were subsequently analyzed using a qualitative juridical method. The findings indicate that the formulation of the APBD constitutes a governmental legal act executed through progressive stages, commencing from the Regional Government Work Plan (Rencana Kerja Pemerintah Daerah - RKPD), the General Budget Policy and Temporary Budget Priority and Ceiling (Kebijakan Umum Anggaran dan Prioritas Plafon Anggaran Sementara - KUA-PPAS), to the Budget Work Plan (Rencana Kerja Anggaran - RKA). The legal standing of the DPRD is manifested through its function of channeling public aspirations, executing the budgetary function, and acting as a co-equal element alongside the Regional Head in regional administration. The enactment of joint approval in determining the APBD serves as a formal validity requirement for regional legal instruments, while simultaneously manifesting the division of authority. The implementation of the APBD in Labuhanbatu Regency necessitates more precise planning synchronization and the capacity strengthening of the DPRD’s budgetary function to prevent budget deficits and discrepancies within planning documents.